2014
DOI: 10.1016/j.jssr.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

“We Have Never Known What Death Was Before” U.S. History Textbooks and the Civil War

Abstract: Textbooks are a significant element of the social studies curriculum and teacher pedagogical choice (Apple, 2004; Apple & Christian-Smith, 1991). Students’ views of American history are dramatically affected by the textbook narratives to which they are exposed, and teachers often tilt their curricular choices based on the textbooks available to them ( Luke, 2006 Schug, Western & Enochs, 1997 ). The history of our nation's armed conflicts is often presented, through our textbooks and our pedagogy, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This potential is reinforced by Djono & Joebagio (2019) in their research, which states that most teachers tend to articulate the importance of unity rather than first raise awareness of diversity. This concern can also occur as American History textbooks experience misinterpretation when teachers explain the abolitionist movement in the Civil War (Pearcy, 2014). This aligns with the finding that a new social cognition is needed to represent the Chinese.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This potential is reinforced by Djono & Joebagio (2019) in their research, which states that most teachers tend to articulate the importance of unity rather than first raise awareness of diversity. This concern can also occur as American History textbooks experience misinterpretation when teachers explain the abolitionist movement in the Civil War (Pearcy, 2014). This aligns with the finding that a new social cognition is needed to represent the Chinese.…”
Section: Discussionmentioning
confidence: 81%
“…If history textbook writing is committed to presenting the Chinese representation, responding appropriately to these various things is necessary. Pearcy (2014), in his research, showed that American History textbooks have misinterpreted the material for the abolitionist movement related to the Civil War, so the teacher's role is decisive in using readers. Learning should not rely solely on textbooks but must create a multifaceted learning experience (Metzger & Harris, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As this study's findings infer, the Just War doctrine can be a useful pedagogical tool, in order to help students consider and attenuate their own views. Just War's classroom uses vary, from its use as a scaffold against which to judge historical acts, contemporary policy, or as a philosophy which itself can be scrutinized (Pearcy, 2013(Pearcy, , 2014. It also makes an effective resource for developing what Joseph (1990) called "conscious, verbalized, and 'chartable' responses" to moral dilemmas (p. 8).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there is a growing qualitative examination of how war is taught. Pearcy (2016Pearcy ( , 2017 has examined student understanding of just war theory and how it is applied to war and how the Civil War has been taught. Pennel (2016) examined how World War I was taught in British schools, and Berman (1988) examined the multiple discourses of the Vietnam War.…”
Section: Teaching Warmentioning
confidence: 99%